2016
DOI: 10.1097/mpg.0000000000001096
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor‐1 Predicts Quantity of Hepatic Steatosis Independent of Insulin Resistance and Body Weight

Abstract: Objective To examine the association between PAI-1, an acute phase protein strongly associated with cardiovascular disease risk, and adiposity, insulin resistance, and inflammation among overweight and obese children with a wide range of hepatic steatosis. Methods Plasma PAI-1 levels were measured in a prospectively recruited cohort of 39 overweight or obese children who underwent comprehensive anthropometric assessment and metabolic measurements. Hepatic steatosis was quantified using magnetic resonance spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…(31) PAI1 has also been reported as a predictor of NASH and NAFLD activity score in obese children (9) and as a predictor of steatosis severity in another cohort. (15) The investigators hypothesized that PAI1 might be involved in NASH hepatic inflammation; indeed tPAI1 retained significance as a predictor in multivariable modeling of lobular inflammation and aPAI1 of portal inflammation in our cohort.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…(31) PAI1 has also been reported as a predictor of NASH and NAFLD activity score in obese children (9) and as a predictor of steatosis severity in another cohort. (15) The investigators hypothesized that PAI1 might be involved in NASH hepatic inflammation; indeed tPAI1 retained significance as a predictor in multivariable modeling of lobular inflammation and aPAI1 of portal inflammation in our cohort.…”
Section: Discussionmentioning
confidence: 60%
“…Most studies did not evaluate NASH histology, instead relying on surrogate markers or imaging as a substitute for diagnosis . Plasminogen activator inhibitor 1 (PAI1) has been associated with NAFLD in three studies in children as well as adult studies; but other markers, including tumor necrosis factor alpha (TNF‐α), interleukin (IL)‐6, IL‐10, and resistin have been inconsistent predictors of NAFLD in smaller cohorts of adults and children (n = 40‐65) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria were currently attempting weight gain or loss, cirrhosis, renal disease/insufficiency, recent acute illness in the past 4 weeks, or pregnancy. More details of the sample are described elsewhere . For most participants (n = 29), plasma samples from baseline were used for metabolomics analysis in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from animal studies indicate a potential role of PAI‐1 in the initiation of NAFLD and demonstrate that reducing PAI‐1 production significantly reverses hepatic steatosis and hepatic lipid accumulation . Our previous study in children showed that PAI‐1 was correlated with the quantity of hepatic steatosis, measured by magnetic resonance spectroscopy, independently of obesity and insulin resistance . However, in that study, as well as the other previous studies in children, no information on severity of inflammation or fibrosis was available, and no lipid markers for CVD risk were reported.…”
Section: Introductionmentioning
confidence: 77%